1995
DOI: 10.1046/j.1365-2648.1995.21040628.x
|View full text |Cite
|
Sign up to set email alerts
|

Search for meaning in long‐term cancer survivors

Abstract: The purpose of this study was to explore search for meaning in long-term survivors of malignant melanoma and the relationship of this meaning to self-blame and well-being. The sample consisted of 31 long-term melanoma survivors who had been free of disease for 5 years or longer. Measures included the Search for Meaning scale, a single item on self-blame and the Index of Well-Being. Data were analysed by descriptive statistics and t-tests. Findings revealed that 52% (n = 16) of the sample did search for meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 14 publications
4
54
0
6
Order By: Relevance
“…Although some studies on cancer patients have found that meaning-focused strategies, such as positive reframing, are related to better subsequent adjustment, such as improved quality of life and psychological wellbeing [35,36], others have reported that searching for meaning is related to poorer adjustment [37,38]. The results of this study show that a brief meaning-focused intervention effectively improves the level of existential wellbeing and quality of life of advanced cancer patients, especially in older people, patients who received inadequate palliative care services and who lack social support, and newly diagnosed patients in the advanced stage of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies on cancer patients have found that meaning-focused strategies, such as positive reframing, are related to better subsequent adjustment, such as improved quality of life and psychological wellbeing [35,36], others have reported that searching for meaning is related to poorer adjustment [37,38]. The results of this study show that a brief meaning-focused intervention effectively improves the level of existential wellbeing and quality of life of advanced cancer patients, especially in older people, patients who received inadequate palliative care services and who lack social support, and newly diagnosed patients in the advanced stage of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Deux de ces thèmes étaient semblables aux conclusions de Howell et collègues (2003), alors que le troisième concernait les changements, à la fois positifs et négatifs, qui étaient survenus dans le système de soins depuis l'annonce du premier diagnostic. Dirksen (1995) a exploré la recherche de signification chez les survivants d'un mélanome malin au moyen de l'échelle de recherche de signification [Search for Meaning scale]. Dirksen (1995) a découvert que 52 % des participants s'étaient livrés à une recherche de signification qui était souvent associée à la recherche d'une cause à l'affection étant donné qu'ils en rejetaient la responsabilité sur eux-mêmes.…”
Section: Expérience) Les Résultats Ont Fait L'objet D'une Interprétaunclassified
“…Dirksen (1995) a exploré la recherche de signification chez les survivants d'un mélanome malin au moyen de l'échelle de recherche de signification [Search for Meaning scale]. Dirksen (1995) a découvert que 52 % des participants s'étaient livrés à une recherche de signification qui était souvent associée à la recherche d'une cause à l'affection étant donné qu'ils en rejetaient la responsabilité sur eux-mêmes. Cette recherche de signification était plus courante chez les participants plus jeunes chez lesquels Dirksen (1995) décrivait la recherche de signification comme étant « un processus cognitif lié au pourquoi de la survenue du cancer et de son impact sur la vie » (p. 633).…”
Section: Expérience) Les Résultats Ont Fait L'objet D'une Interprétaunclassified
See 1 more Smart Citation
“…Search for meaning has been characterized as a prevalent thinking process among those newly diagnosed with a major illness, involving attempts to understand the significance of the diagnosis and redefine meaning in life. Studies show that the majority of cancer patients engage in these processes (52% -87%; Dirksen, 1995;O'Connor et aI., 1990) in an attempt to understand the significance of the diagnosis, while also redefining meaning in life.…”
Section: Situational Meaningmentioning
confidence: 99%